Multi-disciplinary approach for managing plasmacytoma: a case report - Wint Wint Thu Nyunt,; Rahayu Draman,; Aida Widure Mohd Mustapha,; Noralisa Abdul Karim,; Mohd Razif Mohd Idris,; Noraimy Abdullah,; Tang, Yee Loong; Wan Fariza Wan Jamaludin,; Noraidah Masir,; S Fadilah S Abdul Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Solitary plasmacytoma (SP) is a tumor with evidence of clonal plasma cells and no other features of multiple myeloma (MM). We report a case of SP which showed multiple recurrences of SP and then evolution into overt MM. A 56-year-old man presented with the 5-month-history of right nasal obstruction and intermittent epistaxis. He had SP (extraosseous) of right nasopharynx (3.5 × 2 × 2.5 cm), with no paraproteinaemia. He received radiotherapy (56 Gy), achieving complete remission. Ten years later, he had recurrence of SP (osseous) in left tibia, presenting with pathological fracture. He received radiotherapy (50 Gy), achieving partial response. Three years later, he had recurrence of SP (osseous) in right tibia, presenting with right leg pain. He received radiotherapy (45 Gy). While receiving treatment, he had progressive swelling in the area around right eye, double vision and headache. Imaging scans showed multiple plasmacytomas. There were presence of monoclonal paraprotein, hypercalcemia and lytic bone lesions. He was diagnosed as MM (at the age of 70 years) and treated with Bortezomib-based therapy. Currently, after one cycle of treatment, clinical improvement is achieved. The importance of multi-disciplinary team approach for managing patients with plasmacytoma is highlighted in order to achieve the holistic approach of management.